The Prospect and Future of Youth Kroncong Group at Universitas Pendidikan Indonesia in Bandung - Supiarza, Hery; Sobarna, Cece; Sukmayadi, Yudi; Mulyadi, Raden Muhammad (Harmonia: Journal of Arts Research and Education, 2018)
This article discusses the prospect and future of youth Kroncong group at the Indonesia University of Education or Universitas Pendidikan Indonesia in Bandung. The focus of research subject in this study is one particular Kroncong group namely Orkes Kroncong De Oemar Bakrie. By examining the society’s appreciation towards the group performances and by implementing the triangulation techniques; results show that the group can be seen as a representative of youth Kroncong group in Bandung. Based on research from 2000 until 2017, it can be concluded that University-based Kroncong group is more excelled not only in the music industry, but also in the music development and the music organization. The group is considered as a role model and parameter for other youth Kroncong group in Bandung.